Organizational Climate, Organizational Culture and Employee Performance: The Mediating Role of Job Satisfaction - Armanu Armanu; Dodi Wirawan Irawanto; Mega Fianita Fadilah (Universitas Negeri Malang, 2021)
This study aims to analyze the effect of organizational climate and culture on employee performance by mediating job satisfaction. This study includes quantitative research using a questionnaire in data collection. The population in this study were employees of a 3-star hotel in Malang. The sampling technique used non-probability sampling with consecutive sampling types and 146 respondents were selected according to the characteristics of the study. The data analysis technique uses SEM (Structural Equation Modeling, PLS). The study results indicate the two independent variables have different effects on the dependent variable, particularly organizational climate which affects employee performance, while organizational culture does not directly affect employee performance. The results of mediation testing show that job satisfaction provides a mediating role both on the influence of organizational climate and culture on employee performance. This study proposes that hotel management needs to continue to maintain a positive organizational climate and organizational culture so that employees can consider job satisfaction which has an impact on employee performance. Keywords: Organizational climate, organizational culture, job satisfaction, employee performance